When the Medicine Feeds the Problem; Do Nitrogen Fertilisers and Pesticides Enhance the Nutritional Quality of Crops for Their Pests and Pathogens? - Martinez, Daisy A.; Loening, Ulrich E.; Graham, Margaret C.; Gathorne-Hardy, Alfred (Frontiers in Sustainable Food Systems, 2021)
The challenge of maximising agricultural productivity encourages growers to apply high volumes of nitrogen (N) fertilisers and pesticides in order to promote and protect yields. Despite these inputs, pests and pathogens (P&Ps) continue to cause economic losses and challenge food security at local, national and global scales. P&Ps are a particular problem in industrial agricultural environments, where large-scale monocultures facilitate rapid growth of crop-adapted P&P populations. P&P population growth is strongly dependent upon acquisition of N-resources (e.g. amino acids) from crop tissues, and concentrations of these compounds depend on the metabolic state of the crop which, in turn, is influenced by its growth stage, by environmental conditions, and by agrochemical inputs. In this study we demonstrate that routine applications of pesticides and/ or N-fertilisers may inadvertently reinforce the problem of P&P damage in agriculture by enhancing the nutritional quality of crops for these organisms. N-fertilisation has diverse influences on crops’ susceptibility to P&P damage; N-fertilisers enhance the nutritional quality and ‘attractiveness’ of crops for P&Ps, and they can also alter crops’ expression of the defensive traits (both morphological and chemical) that serve to protect them against these organisms. Exposure of crops to pesticides (including commonly used insecticide, fungicide, and herbicide products) can result in significant metabolic disruption and, consequently, in accumulation of nutritionally valuable amino acids within crop tissues. Importantly, these metabolic changes may not cause visible signs of stress or toxicity in the crop, and may represent an ‘invisible’ mechanism underlying persistent P&P pressure in the field. Given the intensity of their use worldwide, their far-reaching and destructive consequences for wildlife and overall ecosystem health, and the continued prevalence of P&P-associated crop damage in agriculture, we recommend that the impacts of these cornerstone agricultural inputs on the nutritional relationship between crops and their P&Ps are closely examined in order to inform appropriate management for a more secure and sustainable food system.